المفهوم الصَّرفيّ للعلل الدَّلاليَّة و القياسيَّة عند الثَّمانيني في كتابه شرح التَّصريف (Journal of Humanitarian and Applied Sciences, 2023)
Morphology is one of the greatest linguistic sciences and the most important of them because of its great care about the structure of the word, and through which the structure of the word and its states are determined that are neither syntactic nor constructive. However, because of the importance of this science, our early scholars took care of it, so they classified books and works in it. Among these scholars is Athamanini (442 AH), one of the scholars of the fifth century AH. The Athamanini is considered one of the most famous students of Ibn Jinni (392 AH). He explained the book “Almalouki fi Attasrif” by his sheikh, Ibn Jinni, which he called Sharh Attasrif, a prolific useful explanation, elaborated on it, and excelled in its explanation. The research presented a brief interpretation of Athamanini, and his book “Sharh Attasrif”, then a definition of the irregularity linguistically and idiomatically, and the emergence and consolidation of the term irregularity. However, the research was limited to two types of irregularities: semantic irregularities, and standard irregularities.